Suicide trends in the early months of the COVID-19 pandemic: an interrupted time-series analysis of preliminary data from 21 countries - Pirkis, J; John, A; Shin, S; DelPozo-Banos, M; Arya, V; Analuisa-Aguilar, P; Appleby, L; Arensman, E; Bantjes, J; Baran, A; Bertolote, JM; Borges, G; et al. (Elsevier, 2021)
Background: The COVID-19 pandemic is having profound mental health consequences for many people. Concerns have been expressed that, at their most extreme, these consequences could manifest as increased suicide rates. We aimed to assess the early effect of the COVID-19 pandemic on suicide rates around the world.